Association of anemia with all-cause mortality in Chinese centenarians: a prospective cohort study - Wangping Jia; Shengshu Wang; Shanshan Yang; Yali Zhao; Qiao Zhu; Chaoxue Ning; Yujian Chen; Shihui Fu; Yizhi Chen; Yao He; Miao Liu (Elsevier, 2024)
Objectives: This study aimed to examine the relationship between anemia and all-cause mortality in Chinese centenarians. Design: Prospective cohort study. Setting and participants: We included 1002 Chinese centenarians from the China Hainan Centenarian Cohort Study (CHCCS) Measurements: Standard procedures were followed to perform blood analysis, home interviews, and physical examinations. Anemia was defined as a hemoglobin level of less than 130 g/L for men and less than 120 g/L for women. Results: During the 9-year follow-up period, a total of 929 (92.7%) deaths were identified. Cox proportional hazards regression models revealed that anemia (hazard ratio [HR] 1.289, 95% confidence interval [CI]: 1.117-1.489) was significantly associated with all-cause mortality. There was an apparent dose-response relationship between anemia and all-cause mortality. Centenarians with severe anemia had approximately 1.6 times higher likelihood of all-cause mortality than those without anemia (HR 1.662; 95% CI: 1.154-2.394). Conclusion: Anemia is associated with an increased risk of all-cause mortality in Chinese centenarians. Further research will be needed to collect more comprehensive data on the etiology of anemia and causes of death in centenarians.